A New Objective Health Numeracy Test for Patients with Type 2 Diabetes: Development and Evaluation of Psychometric Properties - Eun-Hyun Lee; Young Whee Lee; Kwan-Woo Lee; Seongbin Hong; So Hun Kim (Elsevier, 2020)
Purpose: Patients with diabetes frequently need to perform certain numeric tasks such as interpreting blood glucose levels. However, there is no psychometrically sound instrument for objectively measuring diabetes-specific health numeracy. This study aimed to develop a new objective diabetes health numeracy test (DHNT) and evaluate its psychometric properties in adult patients with type 2 diabetes. Methods: An instrument development study was conducted. Initial items were evaluated by six experts for content validity. After a pilot test, a convenience sample of 257 participants with type 2 diabetes was recruited at 2 university hospitals from May to September 2018. The structural, convergent, and criteria validity, and internal consistency of the DHNT with binary item responses were evaluated. Data were analyzed using exploratory factor analysis, Rasch analysis, tetrachoric correlation, Spearman's correlation, and the Kuder-Richardson-20 formula. Results: Exploratory factor analysis yielded a single-factor solution comprising seven items. Rasch analysis confirmed that no item did not fit with the single factor and identified that the item difficulty parameters had moderate values. The convergent and criterion validity of the instrument were demonstrated, with diabetes knowledge and subjective diabetes numeracy, respectively, as was its acceptable internal consistency, by a Kuder-Richardson-20 coefficient of .81. Conclusion: The DHNT demonstrated satisfactory psychometric properties. The instrument with moderate levels of item difficulty may have a lower cognitive burden. The developed instrument can be applied in practice to tailor the education of diabetes self-management as per the levels of health numeracy of specific patients.